Multisystemic Benign Metastasizing Leiomyoma: An Unusual Condition with an Atypical Clinical Presentation. (10th April 2019) - Matos, Fernando; Santiago, Cristina; Silva, Duarte
Abstract : Benign metastasizing leiomyoma (BML) is a rarely found entity with few documented cases in the literature, usually occurring in women of reproductive age with a history of myomectomy or hysterectomy. The leiomyomas can metastasize to several organs, the lungs being the most commonly affected. We report a case of a 40-year-old female patient who presented at our institution with low back pain. She underwent a lumbar MR that revealed the presence of an expansive and compressive mass in the body of L4. This mass was biopsied, corresponding to a metastasizing leiomyoma with no malignant characteristics. Subsequently, a CT examination showed several soft tissue density round masses in both lungs, but the most striking feature was a 12 cm mass located in the left iliac crest. There was asymmetrical uterus enlargement, caused by the presence of several leiomyomas. Since the lesions were estrogen and progesterone positive, hormone suppression consisting of oophorectomy followed by anastrozole was the chosen treatment. No signs of progression were observed at the 6-month follow-up. This case is one of the very few that occurred in a woman with no previous uterine intervention, adding further evidence that surgery is not an essential condition for this entity to develop.